Pengelolaan Kelas pada Pembelajaran Tatap Muka Terbatas di Madrasah Ibtidaiyah - Ramdanil Mubarok (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2024)
The purpose of writing this article is to analyze and interpret classroom management in limited face-to-face learning at Madrasah Ibtidaiyah. The method used is a qualitative research method with the type of library research. As a result, classroom management is essentially an effort made to provide, create and maintain optimal classroom conditions so as to create a good classroom atmosphere that makes it easier for students to learn and understand the subject matter. The implementation of classroom management in face-to-face learning is limited by providing: a) Body temperature measuring devices in class that will be used before students enter class by the way the teacher stands in front of the classroom door, b) Good air circulation in the classroom, c) Room sterilization facilities for spraying disinfectants, d) each student reads their respective learning facilities, e) Applying standard health protocols. Fundamental problems in classroom management problems include: a) disharmony in relationships between students, b) lack of commitment c) negative reactions e) deviations from the provisions, f) unable to work together, do not respect other group members, g) unable to adapt to changes in the learning environment, including in the classroom.